2021
DOI: 10.1111/ipd.12753
|View full text |Cite
|
Sign up to set email alerts
|

Randomised clinical study of plaque removal efficacy of an electric toothbrush in primary and mixed dentition

Abstract: Background Clinical investigations of electric toothbrushes in young children are limited. Aim To assess plaque reduction efficacy of an oscillating‐rotating electric versus manual toothbrush in a paediatric population in primary and mixed dentitions. Design In this randomised, single‐brushing, 2‐treatment, 4‐period, replicate‐use crossover study, subjects were divided into 2 age groups (3‐6 years; 7‐9 years) and assigned to a treatment sequence involving an Oral‐B Kids electric brush and a manual brush contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 18 publications
2
12
0
Order By: Relevance
“…However, group 3 where no intervention was implemented mainly averaged fair in the oral hygiene status. Such results correspond to a study in literature where similar oral hygiene improvement has been found in intellectually disabled children by using oral hygiene educational interventions [ 33 ]. The use of electronic toothbrushes has been studied and proved effective for the better removal of plaque in children.…”
Section: Discussionsupporting
confidence: 91%
“…However, group 3 where no intervention was implemented mainly averaged fair in the oral hygiene status. Such results correspond to a study in literature where similar oral hygiene improvement has been found in intellectually disabled children by using oral hygiene educational interventions [ 33 ]. The use of electronic toothbrushes has been studied and proved effective for the better removal of plaque in children.…”
Section: Discussionsupporting
confidence: 91%
“…The importance of toothbrushing in reducing plaque, gingivitis, and caries in children is well-documented [ 24 , 25 , 26 ]; however, few studies differentiate with regard to the type of toothbrush that might be most beneficial for pediatric populations. While toothbrushing research among children is limited, the findings of this study are consistent with published clinical studies and meta-analyses demonstrating the superior plaque removal efficacy of electric toothbrushes versus manual brushes in young children [ 18 , 19 , 20 ]. Our findings, which are strongly in favor of the oscillating-rotating electric toothbrush, suggest the importance of brush technology type is key to maintaining and improving oral hygiene, managing plaque, and preventing gingivitis.…”
Section: Discussionsupporting
confidence: 86%
“…In this retrospective, cross-sectional study, patient records of 1000 healthy children aged 2.5 to 7 years who visited a pediatric dental clinic in Tel Aviv, Israel from April to June 2019 and met all inclusion criteria, including having complete records, were reviewed by a trained and experienced specialist in pediatric dentistry [ 19 , 20 ]. The sample was limited to 1000 children prior to the study.…”
Section: Methodsmentioning
confidence: 99%
“…In such cases, a powered toothbrush is highly recommended. These toothbrushes can be used more easily and efficiently by parents or nurses when the patient is unable to do so, but different powered toothbrushes are considered expensive, especially in poor countries, and may not be available [6,7]. Many studies have shown that mechanical removal procedures without any chemical factor were effective in reducing dental plaque and gingivitis [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…In such cases, a powered toothbrush is highly recommended. These toothbrushes can be used more easily and efficiently by parents or nurses when the patient is unable to do so, but different powered toothbrushes are considered expensive, especially in poor countries, and may not be available [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%